2010
DOI: 10.3892/mmr.2010.391
|View full text |Cite
|
Sign up to set email alerts
|

Apoptin sensitizes radiation-induced cell death via classic mitochondrial, caspase and p53-dependent signaling in HepG2 cells

Abstract: Abstract. resistance or insensitivity to radiation therapy is one of the hallmarks of hepatocellular carcinoma. Sensitizing radioresistant cancer by combining radiation with other therapeutics to induce apoptosis has been widely investigated. our previous study showed that chicken anaemia virus-derived apoptin protein induced the apoptosis of hepatic carcinoma HepG2 cells. in the present study, we demonstrated that apoptin sensitizes cells to radiation-induced apoptosis using a lentivirus-apoptin expression sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…It is apparent from the crystal structure (Figure 2) that the carbon atom bound to the α-trifluoromethyl group is sp 3hybridized instead of sp 2 -hybridized as shown in 13 (Scheme 2). This alters the mechanism from that predicted in Scheme 2 because an sp 3 -hybridized carbon atom adjacent to the trifluoromethyl group would require that upon inactivation the cofactor would be in the PLP form. High-resolution mass spectrometry was used to identify the cofactor form as PLP (Figure 4), consistent with the crystal structure.…”
Section: ■ Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It is apparent from the crystal structure (Figure 2) that the carbon atom bound to the α-trifluoromethyl group is sp 3hybridized instead of sp 2 -hybridized as shown in 13 (Scheme 2). This alters the mechanism from that predicted in Scheme 2 because an sp 3 -hybridized carbon atom adjacent to the trifluoromethyl group would require that upon inactivation the cofactor would be in the PLP form. High-resolution mass spectrometry was used to identify the cofactor form as PLP (Figure 4), consistent with the crystal structure.…”
Section: ■ Discussionmentioning
confidence: 94%
“…The hydrolysis of 40 gives 43 (via possible intermediates 41 and 42), one of the observed species by intact protein mass spectrometry, and the hydrolysis of 43 gives 44, the other species observed by intact protein mass spectrometry. To obtain the sp 3 -hybridized center at the carbon adjacent to the α-trifluoromethyl group, enolate 42 must be protonated stereoselectively. Given that the iminium proton has broken its phenoxide hydrogen bond and is 2.7 Å from the enol alkene (Figure 8) and because of the geometric constraints of the newly formed covalent bond to Lys292 and the lack of rotatable bonds, we propose an intramolecular stereoselective proton transfer (42) to produce 43, as depicted in Scheme 6.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes it a candidate for the development of novel therapeutic strategies. Studies have revealed that Apoptin is able to kill numerous types of tumor cells, including hepatoma carcinoma cells (1)(2)(3), oral cancer cells (4) and ovarian cancer cells (5). However, the effect of this protein on bladder cancer cells remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This merit has attracted more and more attention from the researchers. Different studies have shown that Apoptin could kill almost all kinds of tumor cells, such as hepatoma carcinoma cells (Han et al, 2008;Han et al, 2010;Han et al, 2011) , oral cancer cells (Schoop, et al, 2008), ovarian cancer cells (Wang et al, 2011). However, the effect of this protein on bladder cancer cells still keep unknown.…”
Section: Introductionmentioning
confidence: 99%